Evaluation and management of systemic corticosteroids-induced ocular hypertension in children with non-Hodgkin lymphoma - Chang, Yitian; Zhang, YuTong; Cui, Zhihua; Jin, Xianmei; Zhao, Yufei; Liang, Lingling; Chang, Jian (Frontiers in Pediatrics, 2022)
Purpose To investigate the effect of systemic corticosteroids (CSs) on ocular hypertension (OHT) and to evaluate the management of OHT in children with non-Hodgkin lymphoma (NHL). Methods Medical records of children with NHL treated in our institution between October 2016 and October 2019 were reviewed. The enrolled patients were divided into the mature B-cell lymphoma (MBL) group and lymphoblastic lymphoma (LBL) group based on pathology. Data on routine ophthalmic examinations and management of OHT were recorded. Results Of the 54 recruited patients, 38 patients (70.4%) had LBL, and 16 (29.6%) had MBL. Thirty-one patients (57.4%) developed OHT, 24 patients (77.4%) in the LBL group, and 7 (22.6%) in the MBL group. Twelve patients (38.7%) were identified as high responders (10 with LBL and 2 with MBL). Symptomatic patients had a higher mean peak IOP than asymptomatic patients (p=0.006). A total of 74.2% of OHT was controlled with antiglaucoma medications (100% in the MBL group vs. 66.7% in the LBL group, significant variation, p<0.001). In total, 8 patients (25.8%) underwent tapering of the CSs dose. The duration of OHT was shorter in the MBL group than in the LBL group (p=0.003). No patients were found to have glaucomatous damage or cataracts. Conclusions Patients receiving systemic CSs had a higher risk of developing OHT, but the pattern of CSs administration might be a critical factor in the risk and severity of OHT. Tapering of CSs dose should be considered the first line for the management of OHT during high-dose CSs therapy.